Castilla y el Concilio de Siena (1423-1424): la embajada regia y su actuación - Villarroel González, Óscar (En la España Medieval, 2007)
Historiographical neglect of the Council of Pavia-Siena (1423-1424) has been particularly acute in the Spanish case. The role Castile played in the council’s bosom has been practically unknown until the present study, which details the actions of the royal embassy of Juan II.